Numerical simulations of liquid-gas-solid three-phase flows in microgravity - Zhang, Xinyu; Ahmadi, Goodarz (SAGE Publishing, 2012)
Three-phase liquid-gas-solid flows under microgravity condition are studied. An Eulerian- Lagrangian computational model was developed and used in the simulations. In this approach, the liquid flow was modeled by a volume-averaged system of governing equations, whereas motions of particles and bubbles were evaluated using the Lagrangian trajectory analysis procedure. It was assumed that the bubbles remained spherical, and their shape variations were neglected. The bubble-liquid, particle-liquid and bubbl- particle two-way interactions were accounted for in the analysis. The discrete phase equations used included drag, lift, buoyancy, and virtual mass forces. Particle-particle interactions and bubble-bubble interactions were accounted for by the hard sphere model. Bubble coalescence was also included in the model. The transient flow characteristics of the three-phase flow were studied; and the effects of gravity, inlet bubble size and g-jitter acceleration on variation of flow characteristics were discussed. The low gravity simulations showed that most bubbles are aggregated in the inlet region. Also, under microgravity condition, bubble transient time is much longer than that in normal gravity. As a result, the Sauter mean bubble diameter, which is proportional to the transient time of the bubble, becomes rather large, reaching to more than 9 mm. The bubble plume in microgravity exhibits a plug type flow behavior. After the bubble plume reaches the free surface, particle volume fraction increases along the height of the column. The particles are mainly located outside the bubble plume, with very few particles being retained in the plume. In contrast to the normal gravity condition, the three phases in the column are poorly mixed under microgravity conditions. The velocities of the three phases were also found to be of the same order. Bubble size significantly affects the characteristics of the three-phase flows under microgravity conditions. For the same inlet bubble number density, the flow with larger bubbles evolves faster. The simulation results showed that the effect of g-jitter acceleration on the gas-liquid-particle three phase flows is small.